2019
DOI: 10.1212/wnl.0000000000007093
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure, glycemic control, and white matter hyperintensity progression in type 2 diabetics

Abstract: Objective To determine whether higher blood pressure mean (BPM) or hemoglobin A1c is associated with progression of white matter hyperintensity (WMH) on MRI in patients with type 2 diabetes, and whether intensive blood pressure or glycemic control can reduce that progression. Methods We performed a secondary analysis of the Action to Control Cardiovascular Risk in Diabetes Memory in Diabetes (ACCORD MIND) research materials. The primary outcome is change in WMH volume (DWMH) between a baseline and month-40 MRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 49 publications
2
62
2
2
Order By: Relevance
“…CSVD is a broad term that refers to pathologies of the cerebral arteries, arterioles, capillaries, and venules [20]. WMH are widely supported to be markers of CSVD associated with aging and CVD [1017]. Yet, our sensitivity analyses showed that the effects of WMH remained after controlling for CVD risk factors (i.e., systolic blood pressure, diagnostic history of hypertension, diabetes, and hypercholesterolemia).…”
Section: Discussionmentioning
confidence: 82%
“…CSVD is a broad term that refers to pathologies of the cerebral arteries, arterioles, capillaries, and venules [20]. WMH are widely supported to be markers of CSVD associated with aging and CVD [1017]. Yet, our sensitivity analyses showed that the effects of WMH remained after controlling for CVD risk factors (i.e., systolic blood pressure, diagnostic history of hypertension, diabetes, and hypercholesterolemia).…”
Section: Discussionmentioning
confidence: 82%
“…Four studies examined the association of duration of DM ( 32 , 33 , 46 , 57 ) and HbA1c values ( 32 , 47 , 50 , 56 ) with WMH, respectively. Christiane Reitz et al ( 56 ) used HbA1c as a continuous variable to define the clinical type of dysglycemia.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, BP control is crucial for the prevention of WMH. Despite the presence of a few conflicting voice, in recent years, emerging evidence has shown the benefit of more intensive BP control in terms of cerebrovascular events and WMH 8‐14 …”
Section: Introductionmentioning
confidence: 99%